The benefits of sectoral diversification for investors with different risk perceptions - Yaman, Serdar; Tuncel, Mert Baran (Elsevier, 2025)
This paper explores the benefits of sectoral diversification in equity investments, comparing traditional and modern portfolio management frameworks for investors with different risk perceptions. We use monthly price data on 200 companies, listed on the Borsa Istanbul, for the period January 2019-August 2024. The analysis employs an equal-weighted (EW) strategy, grounded in traditional portfolio theory, and strategies for risk-averse investors (RAI) and risk-tolerant investors (RTI), based on modern portfolio theory. We find that sectoral diversification can mitigate risks associated with poor performance in a specific sector. Modern portfolio management, which uses both intra-and inter-sectoral diversification, outperforms traditional methods. Our results show that the impact of sectoral diversification on utility maximization differs significantly by the type of investor. For RAI, sectoral diversification provides minimal benefits for maximizing utility, whereas, for RTI, it offers significant advantages. These conclusions are reached based on 11 risk-adjusted performance measurement and a Value-at-Risk analysis.
Keywords: Portfolio management; Sectoral diversification; Investor types